2021
DOI: 10.1542/peds.2021-053129
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth: Improving Access to and Quality of Pediatric Health Care

Abstract: All children and adolescents deserve access to quality health care regardless of their race/ethnicity, health conditions, financial resources, or geographic location. Despite improvements over the past decades, severe disparities in the availability and access to high-quality health care for children and adolescents continue to exist throughout the United States. Economic and racial factors, geographic maldistribution of primary care pediatricians, and limited availability of pediatric medical subspecialists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Recently, the American Academy of Pediatrics (AAP) Section on Telehealth Care, Committee on Practice and Ambulatory Medicine, and Committee on Pediatric Workforce advocated for telehealth as a means of decreasing disparities in access to care by extending paediatric expertise and best practices to children and adolescents no matter where they are located. 12 This is limited, however, by our capacity to address barriers associated with language, digital literacy, special needs, and access to and payment for technology infrastructure. In addition, the AAP argue for payment for telehealth services at parity with the equivalent services provided in-person by private and public insurers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the American Academy of Pediatrics (AAP) Section on Telehealth Care, Committee on Practice and Ambulatory Medicine, and Committee on Pediatric Workforce advocated for telehealth as a means of decreasing disparities in access to care by extending paediatric expertise and best practices to children and adolescents no matter where they are located. 12 This is limited, however, by our capacity to address barriers associated with language, digital literacy, special needs, and access to and payment for technology infrastructure. In addition, the AAP argue for payment for telehealth services at parity with the equivalent services provided in-person by private and public insurers.…”
Section: Discussionmentioning
confidence: 99%
“…Even before the COVID-19 pandemic, digital barriers were known to exist in the United States for diverse populations, non-English speakers, and those with low SES 19. In their policy statement on telehealth, the American Academy of Pediatrics (AAP) notes that lack of high-speed Internet access and other technological resources impedes the delivery of telehealth and increases inequity in access to care 20. To address this divide, the AAP recommends interventions such as using telehealth software that supports smartphone use and integrated language interpretation 21…”
Section: Discussionmentioning
confidence: 99%
“…19 In their policy statement on telehealth, the American Academy of Pediatrics (AAP) notes that lack of highspeed Internet access and other technological resources impedes the delivery of telehealth and increases inequity in access to care. 20 To address this divide, the AAP recommends interventions such as using telehealth software that supports smartphone use and integrated language interpretation. 21 This study demonstrated that, while telemedicine has overall reduced MCOs in pediatric subspecialty care, these increases in access were not equitably distributed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the American Academy of Pediatrics emphasized the growing importance of telehealth services and the need to monitor telehealth's impact on social patterns of healthcare utilization 3 . The early phase of the pandemic was associated with reduced in-person pediatric visits 4 .…”
Section: Introductionmentioning
confidence: 99%